MODELLING THE IMPACTS OF SELECTED WATERSHED MANAGEMENT STRATEGIES ON SEDIMENT REDUCTION UPSTREAM OF SHIRORO DAM, NIGERIA - ADENIYI GANIYU ADEOGUN; HABEEB OLADIMEJI GANIYU; ABRAHAM BABAJIDE OKUNADE; OSENI TAIWO AMOO (Journal of Engineering Studies and Research)
This research utilized a regulated hydrological model, Soil and Water Assessment Tool (SWAT) interfaced with Geographical Information System (GIS), in studying the effectiveness of the chosen watershed management strategies on sediment reduction upstream of Shiroro dam, Nigeria. Selected management approaches were modelled while calibration and validation of the model were achieved using observed streamflow data. Findings indicated a good correlation during calibration and validation period. Application of reforestation, vegetative filter strips and stone bunds in the watershed reduces sediment production by 27 %, 39 %, and 15 % respectively. Thus, the sediment management scenarios depicted within this research are considerably sustainable and effective.